PENINGKATAN KEMAMPUAN BAHASA INGGRIS SISWA MELALUI PROGRAM TERAS BELAJAR DI DESA KOTA NEGARA ILIR - Eny Munisah (Edukasi Lingua Sastra, 2021)
Language is a humans tool for communicating. English is a language that is often used to communicate between countries, English language skills are needed because it is now an era of globalization. Then a way is needed to improve English skills by going through a learning terrace program. Learning terrace program is an English tutoring program for students. The purpose of this activity is to improve the English language skills that can be enjoyed by everyone, especially the lower economic community is needed place that can provide alternative problem solving, namely the existence of free English learning activities that are learning terrace program conducted with facilities that make use of the terrace of people's homes, but do not ignore the quality factors of the results and the process.